Penggunaan Problem Solving untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa SMP - Husna Husna; Fona Fitry Burais (Universitas Syiah Kuala, 2018)
Problem solving is a process or thinking activity to solve a problem. Mathematical problem solving skills is needed for students both in the process of understanding mathematics itself and in everyday life. The problem solving can be achieved by implementing the learning using problem solving approach which train students to deal with various problems including individuals and group problems to be solved individually or together. This learning is oriented towards the investigation and discovery which is basically solving the problems. It is the basis for students to solve problems critically, systematically, logically, and creatively as well as the ability to collaborate effectively and to present fundamental knowledge which in turn can improve the solving skills. This study aimed to examine whether the improvement of mathematical problem solving skills of students learned with the problem-solving approach was better than students taught using the conventional learning. The improvement was examined in general and based on the students’ levels. The study also aimed to investigate an interaction between the learning (problem solving and conventional approach) and student levels (high, medium and low) in increasing mathematical problem solving skills. This study applied a pre-test and post-test control group design. The population of the study were Year 7 students of one of junior high schools in Pidie, Indonesia, consisting of seven classes in 2017/2018. Two classes, a control and an experimental class, were selected as the sample through purposive sampling technique. The instrument used to obtain the data is the mathematical problem solving skills test. The data was then analyzed by employing a two-way ANAVA test using SPSS. The results of the study showed that the improvement of mathematical problem solving skills of the students learning with the problem-solving approach is better than the students experiencing the conventional learning, reviewed in general and based on student levels. There is no interaction between the learning models and student levels on mathematical problem solving skills. The results are expected to be used as a reference for mathematics teachers to apply the problem-solving approach in the learning process to improve mathematical problem solving skills.